Anti-inflammatory effects of manuka honey on salivary cytokines (clinical study) - Al-Kubaisi, Mustafa W.; Al-Ghurabi, Batool H.; Alkubaisy, Waqar; ABDULLAH, Nik N. (Journal of Baghdad College of Dentistry, 2023)
Background: Manuka honey (MH) is a mono-floral honey derived from the Manuka tree (Leptospermum scoparium). MH is a highly recognized for its non-peroxide antibacterial activities, which are mostly related to its unique methylglyoxal content (MGO) in MH. The beneficial phytochemicals in MH is directly related to their favorable health effects, which include wound healing, anticancer, antioxidant, and anti-inflammatory properties. Aims: The purpose of this study was to evaluate the effect of MH on pro-inflammatory cytokines (IL-8 and TNF-α) in patients with gingivitis and compare it with chlorhexidine (CHX) and distilled water (DW). Materials and Methods: This study was a randomized, double blinded, and parallel clinical trial. Forty-five young participants aged (20–40) years were randomly selected and allocated into three groups: MH, CHX, and DW mouthwash groups. Each participant was given a random bottle. Five milliliters each of honey-based mouthwash formulation, CHX mouthwashes (0.2%) and DW were used twice daily for 21 days. All the participants were examined twice, once on the zero day (base line) and once after 21 days. Before and after each participant's mouthwash use IL-8 and TNF-α were measured using enzyme-linked immunosorbent assay (ELISA). Results: The results revealed a drop in the level of interleukin-8 in the manuka honey group which was statistically significant, but the decrease in the same biomarker in the chlorhexidine group was insignificant statistically. TNF-α levels were found to be insignificantly reduced in both the MH and CHX groups (P˃0.05). The DW group, on the other hand, obtained the opposite outcome in both biomarkers. Conclusion: Mouthwash containing MH had an anti-inflammatory impact, indicating an immunomodulatory action. These signs may be encouraging and promising for the use of MH in treating gingivitis.